(untitled) (Eurasian Scientific Herald, 2023)
The article examines the prospects for the introduction of financial technologies in the stock market. Based on the results of the research, scientific conclusions were made on the effective organization of the issuance of securities in thedevelopment of financial markets and the increase and development of its role in the economy